Integrating Information and Media Literacy into Pre-service Special Education Teachers Teaching and Learning - Totok Bintoro; Murni Winarsih (Jurnal Pendidikan dan Pengajaran, 2022)
The rise of the internet and the emergence of new digital devices require information users for information needs, access information effectively and efficiently, applies information, and use information effectively and efficiently. This study aims to develop a model for integrating information and media literacy into pre-service exceptional education learning. The researcher applied the ADDIE approach. This research was conducted with 214 students of the Pre-service Teacher Special Education Program. The methods used to collect data are observation and questionnaires. The instrument used to collect data is a questionnaire. The technique used to analyze the data is quantitative with a rating scale format. The results of the research are that most students have excellent or good information and media literacy skills, both in recognizing to be able to find, access, and retrieve information and media content, understand, assess, and develop information and media, as well as create, utilize needs, and bringing together information and media content. 25.70% of students have very good information and media literacy skills. Most students already have computers with various operating systems and mobile devices such as smartphones, iPods, tablets, and electronic dictionaries. Students consider it essential to improve their digital tools skills because it can enhance learning. It was concluded that the five components of the 5MIL learning model could be used so that students have the competencies needed for 21st-century life.